2006
DOI: 10.1099/vir.0.81328-0
|View full text |Cite
|
Sign up to set email alerts
|

Relaxed template specificity in fowl adenovirus 1 DNA replication initiation

Abstract: The fowl adenovirus 1 (FAdV-1) isolates PHELPS and OTE are highly similar, but have striking differences in the repeat region of the inverted terminal repeat (ITR). Whilst the repeat region in OTE conforms to the conventional human adenovirus repeat region (59-CATCATC), that of PHELPS contains guanidine residues at positions 1, 4 and 7 (59-GATGATG). This implies that the FAdV-1 isolates PHELPS and OTE have either distinct template specificity at replication initiation or, alternatively, a relaxed specificity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In the FAdV-A isolates Phelps and KUR, initiation starts with incorporation of a dGMP. Interestingly, the highly similar FAdV-A strain OTE is conventional and starts initiation by binding of dCMP (Rademaker et al 2006). Studies with minireplicons showed that the pTP and Pol of CELO-OTE and CELOPhelps do not have different specificities, but rather show relaxed template specificity.…”
Section: Viral Replication Proteins the Precursor Tpmentioning
confidence: 99%
See 3 more Smart Citations
“…In the FAdV-A isolates Phelps and KUR, initiation starts with incorporation of a dGMP. Interestingly, the highly similar FAdV-A strain OTE is conventional and starts initiation by binding of dCMP (Rademaker et al 2006). Studies with minireplicons showed that the pTP and Pol of CELO-OTE and CELOPhelps do not have different specificities, but rather show relaxed template specificity.…”
Section: Viral Replication Proteins the Precursor Tpmentioning
confidence: 99%
“…Studies with minireplicons showed that the pTP and Pol of CELO-OTE and CELOPhelps do not have different specificities, but rather show relaxed template specificity. This allows these viruses to use 3 0 -GTAGTAG as well as 3 0 -CTACTAC as templates for replication initiation (Rademaker et al 2006). This implies the efficient formation of pTP-GMP complexes.…”
Section: Viral Replication Proteins the Precursor Tpmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of in vitro replication systems with purified proteins, mainly in the case of bacteriophage φ29 and adenovirus, has allowed the elucidation of the general bases of the protein-priming mechanism of DNA replication ( 2 4 ). Specific initiation proteins interact with the replication origins at both 5′ ends of the genome, partially opening the double helix, exposing a region of ssDNA.…”
Section: Introductionmentioning
confidence: 99%